Sarana Prasarana dan Pembiayaan Penyelenggaraan PAUD dalam Persepektif Manajerial - Neni Komalasari; Dhea Ardiyanti; Sendi Tresa Utami Adi Putri (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Infrastructure and financing are one of the complex problems in the management of Early Childhood Education today. This is caused by the environment of the educational institution itself. The main problem lies in the accumulated need for an ideal management of educational institutions. An ideal educational institution requires a set of references for planning, organizing, implementing, and controlling all available resources to achieve the goals that have been set effectively and efficiently. This study uses a qualitative research method of literature study. Data analysis uses an interactive model by condensing data, presenting data and drawing conclusions or verification. The results showed that the right managerial solution to overcome the problem of facilities and infrastructure as well as Early Childhood Education financing from a managerial perspective was through collaborative management planning. This is because the high need for funding for Early Childhood Education institutions can at least be overcome with various opportunities for financing support that have the potential to be obtained. Various opportunities can be through the government or private parties that are not binding on the Early Childhood Education institution itself. However, despite collaborating with the government and the private sector, the Early Childhood Education institution's commitment to the rules to meet the priority scale is a must. The priority scale of human resource planning, infrastructure and financing must be implemented by Early Childhood Education institutions. This is so that the institution has a balance of financing stability despite changes in social economic conditions.